ANALISIS SIKAP ILMIAH MAHASISWA BIOLOGI PADA PELAKSANAAN PERKULIAHAN EKOLOGI TUMBUHAN TAHUN AKADEMIS 2012/2013 - Yuslim Fauziah; Nursal '; Ici Septifiranta (Biogenesis, 2013)
The research has been carried out that aimed to analyze the student’s scientific in attitude of Biology Education in Education and Teaching Faculty Of Riau University in lecturing of Plant Ecology academic year 2012/2013. This research is a descriptive study conducted on March 25, 2013 until May 11, 2013. The samples in this study were students of Biology Education in Education and Teoching of Riau University that attended in Plant Ecology, amounting to 54 people. The parameter in this study is a scientific attitude with indicator curiosity, discipline, responsibility, and cooperativity on. The results showed that the average scores of students in the scientific attitude delivery of content lecturus was 79.44% (both categories), in discussion groups 85.67% (excellent category) and the practical implementation of 86.05% (excellent category). For in dicators curiosity 82.9%, 87.73% discipline, responsibility 84.73%, 87.67% conscientious, cooperative87.05% all indicators were categorized very well. From these results it can be concluded that the scientific attitude of students in lectures Plant Ecology excellent academic year 2012/2013.Keywords: Plant Ecology Lectures, scientific attitude of students